Penerapan Metode Project Based Learning (PJBL) pada IPAS Tentang Perkembangbiakan Tumbuhan untuk Meningkatkan Hasil Belajar Siswa Kelas IV di SDI Harekakae - Kristina Elisabeth Moruk; Yanuarius Bria Seran; Marianus Teti; Yohana F. Tabun (Jurnal Pendidikan Dirgantara, 2025)
This research aims to improve the learning outcomes of fourth-grade students at SDI Harekakae in Science subject about plant reproduction through the implementation of Project Based Learning (PjBL) method. The research method used is classroom action research (CAR) which was carried out in two cycles. Each cycle consists of planning, action, observation, and reflection. The subjects of the research were fourth-grade students of SDI Harekakae in the academic year of [Academic Year], totaling [Number of Students] students. Data on student learning outcomes were obtained through formative tests at the end of each cycle. The results showed that the implementation of the PjBL method can improve student learning outcomes in plant reproduction material. The improvement of learning outcomes can be seen from the increase in the average class score from cycle I to cycle II. Thus, the PjBL method can be used as an effective learning alternative to improve student learning outcomes in Science subject.